Pendidikan Karakter Anak Melalui Kegiatan Kultur Religius Di Desa Pene Kecamatan Jerowaru - Samsul Bahri (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
Globalization not only promises beautiful hopes, but also raises its own anxieties. In the era of disruption like today, all information is very easy to accept, so without filtering and a strong character foundation, shifts in values ​​such as lack of respect for parents, lack of concern for others begin to occur. This paper aims to explore how children's character education is carried out through religious culture activities in Pene Village, from concept to implementation. This paper is based on qualitative research with primary data sources, namely traditional leaders and leaders of religious activities. The data obtained through the interview method is then interpreted or analyzed. The results of the analysis show that religious cultural activities such as Beqen, yasinan, memorizing short prayers, reading brzanji to memorizing the al-Quran have an important role in shaping the social religious character of children. This is due to the internalization of religious social values ​​such as caring, friendship, social solidarity and so on through civilizing in everyday life. Given the constantly changing and complex nature of the characters, further research is needed to identify problems that have not been identified